NEEDANALYSIS:ALEAPTO DESIGNENGLISHCOURSE CURRICULUM ATPOLITEKNIKPERTANIAN NEGERIPAYAKUMBUH - Hudia Hudia; Yuliandri Yuliandri; Resa Yulita (English Language Education and Current Trends (ELECT), 2023)
This research aimsto analyse the needs of English course curriculum implemented in Politeknik Pertanian Negeri Payakumbuh (henceforth: Politani) as a step to design the new English Course curriculum. Curriculum for vocational study is emphasizing on the mastering of skills rather than mastering the theory of field of studies. Needs analysis regarded as the key point to a successful designing and implementation of certain subject. This study applies two kinds of instruments. The first one is questionnaire distributed to the newly enrolled students asthe respondents to discover their wants. Also, TOEFL Prediction Test was conducted to some new students to check their English competence known as their lacks. There were 237 respondents given the questionnaire sheets as the representative of new students in Politani in 2019. The result of needs analysis showed that respondents wanted to focus the material of English course more on reading and speaking skill as they were aware of both skills were important for their study. In addition, TOEFL Prediction Test result showed that respondents gained the lowest score on reading comprehension section. Meanwhile they achieved higher scores on the listening section. It means that what respondents wants met their lacks in English competence. Researchers then would be able to design the effective and efficient English course curriculum for vocational students in Politani.   REFERENCES Abrar-ul-Hassan, S. (2012). State-of-the-art review: Revisiting the ins and outs of ESP practice. Professional and Academic English, 39, 4-11. Cohen, L., Manion, L., & Morrison, K. (2007). Research methods in education (6th ed.). London: Routledge. Freebody, P. (2003). Qualitative research in education: Interaction and practice. London: Sage. Hutchinson & Waters. (2008). English for Specific Purposes: A Learning-centered Approach. Cambridge: Cambridge University Press. Irianto, Agus. (2012). Statistik:Konsep Dasar, Aplikasi, dan Pengembangannya. Jakarta: Kencana. Kaewpet, C. (2009). A framework for investigating learner needs: Needs analysis extended to curriculum development. Electronic journal of foreign language teaching, 6(2), 209-220 Lie, A. (2009). Education policy and efl curriculum in indonesia: between the commitment to competence and the quest for higher test scores. TEFLIN Journal: A publication on the teaching and learning of English, 18(1).